2020
DOI: 10.1371/journal.pntd.0008831
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the stability of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on skin, currency, and clothing

Abstract: A new coronavirus (SARS-CoV-2) emerged in the winter of 2019 in Wuhan, China, and rapidly spread around the world. The extent and efficiency of SARS-CoV-2 pandemic is far greater than previous coronaviruses that emerged in the 21st Century. Here, we modeled stability of SARS-CoV-2 on skin, paper currency, and clothing to determine if these surfaces may factor in the fomite transmission dynamics of SARS-CoV-2. Skin, currency, and clothing samples were exposed to SARS-CoV-2 under laboratory conditions and incuba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
123
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 14 publications
9
123
2
Order By: Relevance
“…Another option although highly implemented worldwide is to mandate online payments only. There are few studies that have shown the potential risk of handling money in terms of SARS-CoV-2 transmission ( Harbourt et al, 2020 ; Riddell et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option although highly implemented worldwide is to mandate online payments only. There are few studies that have shown the potential risk of handling money in terms of SARS-CoV-2 transmission ( Harbourt et al, 2020 ; Riddell et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other strategies used are the strict use of new face masks, gloves, and hand sanitizers. Delivery workers should wear new face masks and gloves, and frequently apply hand sanitizers to minimize contamination with the novel coronavirus, the use of E-Wallet (i.e., digital) or credit card payment method to limit contact with delivery workers and it is also recommended that customers should discard the packaging as soon as possible and wash hands immediately after ( Harbourt et al, 2020 ; Lee, 2018 ; Martínez, 2019 ; Nguyen and Vu, n.d. ).…”
Section: Resultsmentioning
confidence: 99%
“…We do know that SARS-CoV-2 can survive on skin for hours (half-life of 3 to 5 hours at room temperature). 6,7 Assuming that the SARS-CoV-2-infected visitor leaves your office within the hour, the virus Downloaded from https://www.cambridge.org/core. 22 Feb 2021 at 01:03:18, subject to the Cambridge Core terms of use.…”
Section: Is This Position Based On Data and If So What Data?mentioning
confidence: 99%
“…A 72-hour time frame was selected as it coincides with a common work schedule observed by many intensive care unit personnel (e.g., nurses) in the United States (three 12-hour shifts worked over three consecutive days of the week) who may need to reuse PPE day after day because of PPE shortages. Forceps were used to collect samples and place them into 2 mL tubes containing media as previously described, 5 after which forceps were disinfected between samples using 5% MicroChem™ Plus followed by 70% ethanol. Samples were then stored at −80°C before quantification of infectious virus.…”
mentioning
confidence: 99%